2019
DOI: 10.1029/2018jd029296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Energetic Electron Precipitation on the Northern Polar Vortex: Explaining the QBO Modulation via Control of Meridional Circulation

Abstract: Energetic electron precipitation (EEP) affects the high‐latitude middle atmosphere by producing NOX compounds that destroy ozone. Earlier studies have shown that in the wintertime polar stratosphere, increased EEP enhances the westerly wind surrounding the pole, the polar vortex. This EEP effect has been found to depend on the quasi‐biennial oscillation (QBO) of equatorial winds, but the mechanism behind this modulation has so far remained unresolved. In this study we examine the atmospheric effect of EEP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 44 publications
19
50
1
Order By: Relevance
“…In fact SSW occurrence rate is highest in winters with low Ap (low EEP) and QBO-E, when SSW occurs in 15 out of 17 winters. This result agrees with earlier studies (Maliniemi et al, 2013(Maliniemi et al, , 2014(Maliniemi et al, , 2016(Maliniemi et al, , 2018Salminen et al, 2019) showing that the effect of energetic electron precipitation on polar vortex is stronger in QBO-E winter months. In QBO-E winters low EEP weakens the polar vortex and SSWs occur more often, while high EEP strengthens the polar vortex and SSWs occur less.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact SSW occurrence rate is highest in winters with low Ap (low EEP) and QBO-E, when SSW occurs in 15 out of 17 winters. This result agrees with earlier studies (Maliniemi et al, 2013(Maliniemi et al, , 2014(Maliniemi et al, , 2016(Maliniemi et al, , 2018Salminen et al, 2019) showing that the effect of energetic electron precipitation on polar vortex is stronger in QBO-E winter months. In QBO-E winters low EEP weakens the polar vortex and SSWs occur more often, while high EEP strengthens the polar vortex and SSWs occur less.…”
Section: Discussionsupporting
confidence: 93%
“…It is hard to distinguish at which pressure level QBO fundamentally affects SSW occurrence, but the most robust and significant difference (p < 0.01) in SSW occurrence between the QBO phases is found for August-October values of QBO at 30 hPa and June QBO at 20 hPa. Salminen et al (2019) found that the meridional circulation into the northern polar stratosphere and the EEP effect on polar vortex are stronger in QBO-E than in QBO-W phase if the QBO at 30 hPa of previous August-September is used to determine the QBO phases. Figure 3 shows the number of winters with (red) and without (blue) SSWs in cases where winters are separated both according to QBO and one of the other variables (Ap, ENSO or SSN).…”
Section: Ssw Occurrence Rate Dependence On Internal and External Varimentioning
confidence: 99%
“…These lags for Ap are thus employed in all analyses. Similar time lags were already previously found optimal (Maliniemi et al, , ; Salminen et al, ) and agree with the time it takes for majority of NO x /NO y created by energetic particle precipitation to descend from the mesosphere to the stratosphere (Funke et al, , ). Note that these lags also correspond well to the effective lags, which Funke et al () found optimal for correlation between EPP produced NO y in the stratosphere/lower mesosphere and the Ap index.…”
Section: Methodssupporting
confidence: 89%
“…After this procedure the significance of regression parameters can be calculated using Student's t-test (this would not be correct with the autocorrelative residual term). A detailed description of the regression model and its benefits can be obtained in our recent articles (Maliniemi et al, 2018;Salminen et al, 2019).…”
Section: Datasets and Statistical Methodsmentioning
confidence: 99%